Aids in the elderly: reasons that lead to late diagnosis - Alencar, Rubia Aguiar [UNESP]; Ciosak, Suely Itsuko (Assoc Brasileira Enfermagem, 2016)
Objective: to investigate elderly living with HIV/Aids and health professionals, what are the reasons that lead to late diagnosis of HIV infection in the elderly. Method: prospective, qualitative study, conducted at a specialized outpatient clinic with elderly living with HIV/Aids, diagnosed age over 60 years and in the Family Health Strategy units with nurses and physicians. Data were collected through interviews and verified by content analysis, using the theoretical framework of vulnerability. Results: a total of 11 elderly, 11 nurses and 12 physicians participated in the study. Three empirical categories emerged: the late diagnosis of HIV happens against the health service; invisibility of the sexuality of the elderly; and weaknesses in the anti-HIV serology request for the elderly. Conclusion: there are health professionals who see the elderly as asexual, causing the diagnosis of HIV to happen in the secondary and tertiary service instead of primary care.
Keywords: Aged; HIV; Delayed Diagnosis; Disaster Vulnerability; Health Personnel